In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Modulating IL-1β-induced pro-atherogenic endothelial responses through drug repurposing - Kundan Solanki; Sk Rameej Raja; Sunanda Samanta; P. S. Shishira; Anjali Roy; Parimal Kar; Swati Biswas; K. M. Ramkumar; Mirza S. Baig (Inflammopharmacology, 2026)

Discovery of two new tirucallane-type triterpenes anomers from Toona ciliata - Aliya Tabassum; Harshad B. Bhore; Jayanta Samanta; Anil Kumar Katare; Yogesh P. Bharitkar (Natural Product Research, 2026)

Discussion: ‘Exploratory modelling of the impacts of sea-level rise on the Sundarbans mangrove forest, West Bengal, India’ by Samanta et al. (2023) Response to comment by Das and Bandyopadhyay (2025) Science of the Total Environment 972, 178937 - Sourav Samanta; Sugata Hazra; Jon R. French; Robert J. Nicholls; Partho P. Mondal (Science of The Total Environment, 2026)

Satellite retrieval of phytoplankton size class biomass: algorithm evaluation and long-term patterns in the northern Arabian Sea - Sanjiba Kumar Baliarsingh; Alakes Samanta; P. Minu; S. Ayana; Aneesh A. Lotliker (International Journal of Remote Sensing, 2026)

Molecular Epidemiology of Multi-Drug Resistant E. coli Isolated from Poultry Birds in Six Agroclimatic Zones of West Bengal, India: A Cross-Sectional Study - Md Habib; J. Banerjee; S. Batabyal; P. K. Nanda; A. K. Das; U. K. De; I. Samanta; P. Dandapat; S. Bandyopadhyay (Indian Journal of Microbiology, 2025)

Short‐Term Prediction of Hilsa ( Tenualosa ilisha ) Catch in the Northern Bay of Bengal Using Advanced Machine Learning Algorithms - Sandip Giri; A. P. Joshi; Prasanna Kanti Ghoshal; Sudheer Joseph; Kunal Chakraborty; Alakes Samanta; T. M. Balakrishnan Nair; T. Srinivasa Kumar (Fisheries Oceanography, 2025)
Hilsa is a vital transboundary fishery resource in the Bay of Bengal (BoB), holding commercial, ecological, and cultural importance. This study aims to develop a short‐term prediction of Hilsa catch in the northern BoB using a machine learning (ML) model. The prediction technique was developed considering the georeferenced Hilsa catch per unit effort (CPUE) as a function of environmental variables like surface salinity, sea surface temperature (SST), surface current speed, and direction. We employed two advanced ML algorithms, viz., random forest (RF) and 5. (XGBoost) to examine their efficacy in the short‐term prediction of Hilsa for the northern BoB and compared the model performance with a baseline information obtained through multiple linear regression (MLR). Our analysis showed significant improvement in the prediction accuracy using advanced ML techniques where XGBoost again outperformed RF. The root mean square error (RMSE) values between observed and predicted CPUE for RF and XGBoost models were 5.72 and 5.63 kg/h, respectively. The correlation coefficient (r) between the observed and predicted catch were 0.90 and 0.93 for RF and XGBoost, respectively. SHapley Additive exPlanations (SHAP) analysis revealed the highest influence (58.38%) of surface current speed on the Hilsa CPUE. We generated the spatial prediction maps of Hilsa CPUE using the best performing (XGBoost) model with 85% prediction efficiency. This study showed the potential of the XGBoost model in developing a short‐term prediction for Hilsa in the northern BoB, towards developing Hilsa fishery advisory for sustainable management of these fishery resources.

Monsoonal influence on floating marine litter pathways in the Bay of Bengal - Lianne C. Harrison; Jennifer A. Graham; Piyali Chowdhury; Tiago A. M. Silva; Danja P. Hoehn; Alakes Samanta; Kunal Chakraborty; Sudheer Joseph; T. M. Balakrishnan Nair; T. Srinivasa Kumar (Ocean Science, 2025)
Marine litter in the Bay of Bengal has been under-studied despite large quantities of mismanaged waste reportedly entering the ocean from its surrounding countries. The seasonal reversal of monsoon currents in this region provides a unique environment for the transport of floating macro-litter. A particle tracking model is used here to investigate source-to-sink connectivity of marine debris between countries via oceanic pathways in the Bay of Bengal. We use an approach considering uniform release of particles along the entire coastline, avoiding the considerable uncertainties associated with assumed riverine sources. Two different simulations are considered, forced with either a high-resolution ocean hindcast developed specifically for the Bay of Bengal or a lower-resolution dataset which includes data assimilation. The vast majority of particles released during our simulations were found to beach within 16 months; most particles beached in their country of origin (57 %–90 %), with connectivity towards Myanmar accounting for the second highest connectivity rates (2 %–29 %) from many countries within the Bay of Bengal. This is likely due to the relatively large size of Myanmar's coastline and that it lies in the path of the East India Coastal Current for much of the year (February–September). Patterns of connectivity were found to change along with the monsoon and the post-monsoon period (October–January) showed a notably greater dispersal of particles than the rest of the year. Both simulations were evaluated using the pathways of undrogued surface drifters, which moved primarily within the open ocean, with better agreement found here for particles advected by data-assimilated ocean velocities. This study will therefore crucially inform future research and policy in this region, providing advice on the benefits and suitability of selecting different modelling approaches independent of assumptions of the source locations or volumes.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Tide–surge interaction observed at Singapore and the east coast of Peninsular Malaysia using a semi-empirical model - Zhi Yang Koh; Benjamin S. Grandey; Dhrubajyoti Samanta; Adam D. Switzer; Benjamin P. Horton; Justin Dauwels; Lock Yue Chew (Ocean Science, 2024)
Tide–surge interaction plays a substantial role in determining the characteristics of coastal water levels over shallow regions. We study the tide–surge interaction observed at seven tide gauges along Singapore and the east coast of Peninsular Malaysia, focusing on the timing of extreme non-tidal residuals relative to tidal high water. We propose a modified statistical framework using a no-tide–surge interaction (no-TSI) null distribution that accounts for asymmetry and variation in the duration of tidal cycles. We find that our modified framework can mitigate false-positive signals of tide–surge interaction in this region. We find evidence of tide–surge interaction at all seven locations, with characteristics varying smoothly along the coastline: the highest non-tidal residuals are found to occur most frequently before tidal high water in the south, both before and after tidal high water in the central region, and after tidal high water in the north. We also propose a semi-empirical model to investigate the effects of tidal-phase alteration, which is one mechanism of tide–surge interaction. Results of our semi-empirical model reveal that tidal-phase alteration caused by storm surges is substantial enough to generate significant change in the timing of extreme non-tidal residuals. To mitigate the effect of tidal-phase alteration on return level estimation, skew surge can be used. We conclude that (1) tide–surge interaction influences coastal water levels in this region, (2) our semi-empirical model provides insight into the mechanism of tidal-phase alteration, and (3) our no-TSI distribution should be used for similar studies globally.

Pathways of ice multiplication in nimbostratus clouds during the Indian summer monsoon - Gokul Kavil Kambrath; K. Gayatri; Sachin Patade; Soumya Samanta; Y. Jayarao; P. Murugavel; J. Sandeep; T.V. Prabhakaran (Atmospheric Research, 2024)

Recombinant 3AB3 nonstructural protein-based indirect ELISA for detection of foot-and-mouth disease virus infection-elicited antibodies in goat - M. Rout; L. K. Pandey; B. R. Prusty; R. Samanta; J. K. Mohapatra; R. P. Singh (Veterinary Research Communications, 2024)

Effects of aerosols on the lifecycle of a mesoscale cloud cluster over the Indian peninsula: A numerical study with a bin-based cloud microphysics scheme - Soumya Samanta; Gayatri Kulkarni; P. Murugavel; P. Suneetha; Thara V. Prabha (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Exploratory modelling of the impacts of sea-level rise on the Sundarbans mangrove forest, West Bengal, India - Sourav Samanta; Sugata Hazra; Jon R. French; Robert J. Nicholls; Partho P. Mondal (Science of The Total Environment, 2023)

Occurrence of canine parvovirus type 2c in diarrhoeic faeces of dogs in Kolkata, India - S. Abhiram; T. Mondal; S. Samanta; K. Batabyal; S. N. Joardar; I. Samanta; D. P. Isore; S. Dey (VirusDisease, 2023)

Antibacterial effect of kitchen herbs against pathogenic multidrug-resistant E. coli isolates from calf diarrhoea - Saroj Rai; M. Kumar; R. Jas; G. P. Mandal; I. Samanta; M. Rajendar; S. Tripura; S. K. Das; M. Mondal; D. K. Mandal (Tropical Animal Health and Production, 2023)

Aetiology and molecular characterization of the pathogens associated with soft rot disease of Aloe vera (L.) Burm. f. - Ram Prasnna Meena; Kunal Mandal; Mital P. Patel; Dipal Minipara; Jatin N. Samanta (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

A simple but improved protocol for measuring carbon and oxygen isotope ratios of calcite in calcite-dolomite mixtures - Sruthi P. Sreenivasan; Melinda Kumar Bera; Arpita Samanta (Applied Geochemistry, 2023)

Morphological and microphysical characteristics associated with the lifecycle of a stationary cloud cluster during the Indian Summer Monsoon: A comparative study with numerical simulations and radar observation - Soumya Samanta; Thara V. Prabha; P. Murugavel; P. Suneetha (Atmospheric Research, 2023)

Systomus spilurus (Günther, 1868) Cyprinidae, A New Distribution Record from Narmada Riverine Biodiversity, Gujarat, India - Dibakar Bhakta; B. K. Das; Suhas P. Kamble; Sonia Solanki; Debarghya Maji; A. K. Sahoo; S. Samanta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Pelican–Tilapia interaction in Salton sea: an eco-epidemiological model with strong Allee effect and additional food - Sudeshna Mondal; G. P. Samanta (Modeling Earth Systems and Environment, 2022)

Finfish Diversity of River Narmada and Its Tributaries - Dibakar Bhakta; Sonia Solanki; Nirali Vadhel; W. Anand Meetei; Suhas P. Kamble; G. Chandra; S. Samanta; B. K. Das (Proceedings of the Zoological Society, 2020)

Metal contaminations in sediment and associated ecological risk assessment of river Mahanadi, India - S. Samanta; Vikas Kumar; S. K. Nag; R. K. Raman; K. Saha; S. Bandyopadhyay; B. P. Mohanty; B. K. Das (Environmental Monitoring and Assessment, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Azomethine ylide cycloaddition: a versatile tool for preparing novel pyrrolizidino-spiro-oxindolo hybrids of the doubly conjugated alkamide piperine - Meenakshi Singh; A. V. Amrutha Krishnan; Ramkrishna Mandal; Jayanta Samanta; V. Ravichandiran; Ramalingam Natarajan; Yogesh P. Bharitkar; Abhijit Hazra (Molecular Diversity, 2020)

A First Global Oceanic Compilation of Observational Dissolved Aluminum Data With Regional Statistical Data Treatment - Jan-Lukas Menzel Barraqueta; Saumik Samanta; Eric P. Achterberg; Andrew R. Bowie; Peter Croot; Ryan Cloete; Tara De Jongh; Maria D. Gelado-Caballero; Jessica K. Klar; Rob Middag; Jean C. Loock; Tomas A. Remenyi; et al. (Frontiers in Marine Science, 2020)

Case Study of a Convective Cluster Over the Rain Shadow Region of Western Ghats Using Multi-platform Observations and WRF Model - Soumya Samanta; Kulkarni Gayatri; P. Murugavel; B. Balaji; N. Malap; Y. Jaya Rao; S. M. Deshpande; S. M. Sonbawne; P. Suneetha; Thara V. Prabha (Pure and Applied Geophysics, 2020)

A Review on Basic Biology of Bacterial Biofilm Infections and Their Treatments by Nanotechnology-Based Approaches - Debjani Banerjee; P. M. Shivapriya; Pavan Kumar Gautam; Krishna Misra; Amaresh Kumar Sahoo; Sintu Kumar Samanta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Local dynamics of a predator–prey community in a moderate period of time - Sangeeta Saha; G. P. Samanta (Energy, Ecology and Environment, 2020)

Dynamical behaviour of a two-prey and one-predator system with help and time delay - Sudeshna Mondal; G. P. Samanta (Energy, Ecology and Environment, 2020)

Assessment of adverse impacts of glyphosate-based herbicide, Excel Mera 71 by integrating multi-level biomarker responses in fishes - P. Samanta; S. Pal; A. K. Mukherjee; T. Senapati; J. Jung; A. R. Ghosh (International Journal of Environmental Science and Technology, 2019)

Generation of common coefficients to estimate global solar radiation over different locations of India - Suman Samanta; Pulak Kumar Patra; Saon Banerjee; Lakshmi Narsimhaiah; M. A. Sarath Chandran; P. Vijaya Kumar; Sanjib Bandyopadhyay (Theoretical and Applied Climatology, 2019)

Slope stability assessment and design of remedial measures for Tungnath Temple at Uttarakhand, India: a case study - M. Samanta; P. Punetha; S. Sarkar; A. Dwivedi; M. Sharma (Natural Hazards, 2019)

Palaeocene–Eocene carbon isotopic excursion from the shallow-marine-carbonate sequence of northeast India: Implications on the CIE magnitude and geometry - Sruthi P Sreenivasan; Melinda Kumar Bera; Arpita Samanta; Ravikant Vadlamani (Journal of Earth System Science, 2018)

Trace metal concentrations in euryhaline fish species from Chilika lagoon: human health risk assessment - S. Parida; S. K. Barik; B. Mohanty; P. R. Muduli; S. K. Mohanty; S. Samanta; A. K. Pattanaik (International Journal of Environmental Science and Technology, 2017)

Association between vitamin deficiency and metabolic disorders related to obesity - Samanta Thomas-Valdés; Maria das Graças V. Tostes; Pamella C. Anunciação; Bárbara P. da Silva; Helena M. Pinheiro Sant'Ana (Critical Reviews in Food Science and Nutrition, 2017)

Metal homeostasis in bacteria: the role of ArsR–SmtB family of transcriptional repressors in combating varying metal concentrations in the environment - Rudra P. Saha; Saikat Samanta; Surajit Patra; Diganta Sarkar; Abinit Saha; Manoj Kumar Singh (BioMetals, 2017)

Dynamics of a food chain model with herd behaviour of the prey - S. P. Bera; A. Maiti; G. P. Samanta (Modeling Earth Systems and Environment, 2016)

On the stability and Hopf-bifurcation of a multi-delayed competitive population system affected by toxic substances with imprecise biological parameters - D. Jana; P. Dolai; A. K. Pal; G. P. Samanta (Modeling Earth Systems and Environment, 2016)

Extratropical anticyclonic Rossby wave breaking and Indian summer monsoon failure - Dhrubajyoti Samanta; M. K. Dash; B. N. Goswami; P. C. Pandey (Climate Dynamics, 2016)

Experimental Lung Injury Promotes Changes in Oxidative/Nitrative Status and Inflammatory Markers in Cerebral Cortex of Rats - Maira J. da Cunha; Aline A. da Cunha; Samanta O. Loureiro; Fernanda R. Machado; Felipe Schmitz; Janaína Kolling; Eduardo P. Marques; Angela T. S. Wyse (Molecular Neurobiology, 2015)

Changes in serotonin transporter (5-HTT) gene expression in peripheral blood cells after MDMA intake - Samanta Yubero-Lahoz; K. P. C. Kuypers; J. G. Ramaekers; Klaus Langohr; Magí Farré; Rafael de la Torre (Psychopharmacology, 2015)

Evidence of gas hydrate accumulation and its resource estimation in Andaman deep water basin from seismic and well log data - Anand Prakash; B. G. Samanta; N. P. Singh (Marine Geophysical Research, 2013)

k nearest neighbor-molecular field analysis on human HCV NS5B polymerase inhibitors: 2,5-disubstituted imidazo[4,5-c]pyridines - S. P. Gupta; S. Samanta; Neeraj Masand; Vaishali M. Patil (Medicinal Chemistry Research, 2013)

3D QSAR kNN-MFA studies on thiouracil derivatives as hepatitis C virus inhibitors - Vaishali M. Patil; S. P. Gupta; S. Samanta; Neeraj Masand (Medicinal Chemistry Research, 2011)

A seismic study to investigate the prospect of gas hydrate in Mahanadi deep water basin, northeastern continental margin of India - Anand Prakash; B. G. Samanta; N. P. Singh (Marine Geophysical Research, 2010)

Characterization of Vibrio species isolated from freshwater fishes by ribotyping - P. Mishra; M. Samanta; S. Mohanty; N. K. Maiti (Indian Journal of Microbiology, 2010)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)